Strategi Pembelajaran Kontekstual dalam Mengembangkan Sikap Toleransi Gen Z di Sekolah Islam - Resti Yulastri; Putri Ramadhon; Annisa Annisa; Dwi Herliani; Siti Saroh Hasibuan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The rapid transformation of education driven by globalization and technological advancement demands adaptive learning approaches that align with the characteristics of Generation Z learners. This generation is known for its curiosity, independence in thinking, and openness to diverse perspectives, yet it is also vulnerable to misinformation and negative online influences. Within the context of Islamic education, learning is not solely oriented toward cognitive development but also emphasizes the cultivation of moral values, particularly tolerance. This study aims to explore how contextual teaching methods can contribute to fostering tolerant attitudes among Generation Z students in Islamic educational settings. The research employs a qualitative approach through library research, utilizing a descriptive-analytical framework. Data were collected from various sources, including academic journals, books, and previous studies related to contextual learning, multicultural education, and Generation Z characteristics. The data collection technique involved document analysis, followed by content analysis procedures such as data reduction, categorization, and conclusion drawing. The findings indicate that contextual learning effectively promotes tolerance by engaging students in discussion, problem-solving, reflection, and real-life experiences. The integration of multicultural values and the role of teachers as facilitators and role models further strengthen this process. However, challenges remain, including limited teacher understanding, the persistence of conventional methods, inadequate supporting facilities, and the influence of social media. Overall, contextual learning presents a relevant strategy for developing open-minded, balanced, and socially adaptive Generation Z learners.